The first annotated checklist of Croatian crickets and grasshoppers (Orthoptera: Ensifera, Caelifera) - Skejo, Josip; Rebrina, Fran; Szövényi, Gergely; Puskás, Gellért; Tvrtković, Nikola (Zootaxa, 2018)
The first annotated checklist of crickets and grasshoppers (Orthoptera) of Croatia is presented. With 184 orthopteran species, 103 Ensifera and 81 Caelifera, known to inhabit the country, Croatia is among the richest European countries in terms of Orthoptera diversity. Altogether 25 species erroneously reported from the country are omitted from the checklist, 16 Ensifera (Isophya speciosa, Poecilimon brunneri, P. jonicus, P. thoracicus, Modestana ebneri, Pachytrachis bosniacus, Rhacocleis neglecta, Tessellana carinata, T. nigrosignata, Zeuneriana marmorata, Pteronemobius lineolatus, Myrmecophilus acervorum, M. ochraceus, Dolichopoda palpata, Diestrammena asynamora, Troglophilus brevicauda) and 9 Caelifera (Tetrix kraussi, Paracaloptenus caloptenoides, Chorthippus albomarginatus, Omocestus viridulus, Pseudochorthippus montanus, Miramella alpina, Celes variabilis, Oedipoda germanica, O. miniata). First faunistic records of 10 taxa are reported for Croatia, in total four Ensifera (Leptophyes punctatissima, Metrioptera hoermanni, Zeuneriana amplipennis, Gryllotalpa sp.) and six Caelifera (Xya variegata, Chorthippus dichrous, C. loratus, C. mollis ignifer, Odontopodisma sp., Acrotylus l. longipes). For each listed species, its distribution in Croatia and in Europe is given, and IUCN European Red List status is shown for species within threatened categories. Numerous distributional, taxonomic and nomenclatural problems are discussed. Several taxa with poorly defined diagnostic traits are synonymized, namely Gampsocleis abbreviata renei syn.nov. (with G. a. abbreviata), Pholidoptera maritima syn.nov. (with P. dalmatica), P. brachynota syn.nov. (with P. dalmatica), Acrida m. mediterranea syn.nov. (with A. u. ungarica), Chrysochraon dispar intermedius syn.nov. (with C. d. giganteus) and Odontopodisma rammei syn.nov. (with O. fallax).